Obesity and colorectal cancer risk in women. Issue 2 (1st August 2002) - Terry, P D; Miller, A B; Rohan, T E
Abstract : Background: Several large studies of obesity and colorectal cancer risk have found no association among women but a reasonably consistent positive association among men. In women, a positive association that is stronger among, or limited to, those who are premenopausal has been suggested by studies that stratified analyses by age, although no previous study has examined the association by menopausal status. Methods: We used proportional hazards analyses to estimate hazard ratios relating obesity to colorectal cancer risk among 89 835 women aged 40–59 years at recruitment into the Canadian National Breast Screening Study, a multicentre randomised controlled trial of mammography screening for breast cancer. During an average 10.6 years of follow up (936 433 person years), a total of 527 women were diagnosed with incident colorectal cancer (363 colon and 164 rectal). Results: We found that obesity (body mass index ≥30 kg/m 2 ) was associated with an approximately twofold increased risk of colorectal cancer among women who were premenopausal at baseline (hazard ratio 1.88, 95% confidence interval 1.24–2.86). There was no association among postmenopausal women (p for interaction=0.01), and there was only a weak positive association in the entire cohort. Conclusions: Our data suggest that obesity is associated with a twofold increased risk of colorectal cancer in premenopausal women but is not associated with altered risk in postmenopausal women. Effect modification by menopausal status may better explain the inconsistent or weak findings in previous studies than the presumed lack of an association among women.